The Deradicalization Program to Reduce Criminal Acts of Terrorism in Indonesia: A Mixed Method Approach - Rozikin, Mochammad; Sipayung, Aswin; ., Sumartono; Saleh, Choirul; Riyadi, Bambang Slamet (International Journal of Membrane Science and Technology, 2023)
This research aims to understand the Deradicalization Program to Reduce Criminal Acts of Terrorism in Indonesia that are very interesting to be studied due at the ontological level and sociological level based on Collaborative Governance Perspective. The problem was analyzed using a mixed method study. Data were collected through interview, observation, documentation, and survey questionnaire. Data were analyzed using qualitative data analysis consisting of data reduction, data display, and data verification, triangulation, and a quantitative data analysis using smartPLS application. The results indicate that Deradicalization Program to Reduce Criminal Acts of Terrorism in Indonesia are needed for providing information to stakeholders and inputs for state agencies as public officials and practitioners in making better regulation and policy.